Houses in Herculaneum : A new View on the Town Planning and the Building of Insulae III and IV - Kind, Richard E.L.B. de, (Circumvesuviana ;, 1998)
In this study a new view is given on the city-plan of ancient Herculaneum, by combining the evidence from the ancient writers, the 19th century explorations and the analysis of the measurements of the excavated house-blocks ('insulae'). Furthermore, it contains a detailed examination of the southernmost insulae III and IV, with surprising results. First of all the allotment of these two insulae is made visible, which gives way to a discussion about the division of land in pre-Roman Campania. Furthermore, the author distinguishes some new types of houses, which differ from the already known atrium buildings.